2013
DOI: 10.1371/journal.pone.0052459
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression and Characteristics of a Novel Alkalistable and Thermostable Xylanase Encoding Gene (Mxyl) Retrieved from Compost-Soil Metagenome

Abstract: BackgroundThe alkalistable and thermostable xylanases are in high demand for pulp bleaching in paper industry and generating xylooligosaccharides by hydrolyzing xylan component of agro-residues. The compost-soil samples, one of the hot environments, are expected to be a rich source of microbes with thermostable enzymes.Methodology/Principal FindingsMetagenomic DNA from hot environmental samples could be a rich source of novel biocatalysts. While screening metagenomic library constructed from DNA extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 55 publications
5
56
0
Order By: Relevance
“…Microbial diversity in this habitat, as shown by clonal library analysis (24) and tagged 16S rRNA pyrosequencing (15) revealed novel and complex microbial communities with high metabolic potential on lignocellulose degradation. Activity screening based on target enzyme function has been demonstrated to be useful for identifying genes and gene clusters encoding various glycosyl hydrolases and auxiliary enzymes involved in biomass degradation from various environments, e.g., soil (25), rumen (26), and termite gut (10). On the one hand, activity-based screening is limited by differences among species in codon usage, transcription and translation signals, protein folding elements, and post-translational modification, which affect heterologous expression in E. coli host.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial diversity in this habitat, as shown by clonal library analysis (24) and tagged 16S rRNA pyrosequencing (15) revealed novel and complex microbial communities with high metabolic potential on lignocellulose degradation. Activity screening based on target enzyme function has been demonstrated to be useful for identifying genes and gene clusters encoding various glycosyl hydrolases and auxiliary enzymes involved in biomass degradation from various environments, e.g., soil (25), rumen (26), and termite gut (10). On the one hand, activity-based screening is limited by differences among species in codon usage, transcription and translation signals, protein folding elements, and post-translational modification, which affect heterologous expression in E. coli host.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant T inact values 10-158C > T opt . Details can be found in [63,64,67,68]. Abbreviations: T inact , temperature at which enzyme are 50% inactive; T opt , optimum temperature for activity.…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…A large number of hyperthermophilic enzymes capable of hydrolyzing lignocellulosic biomass have been cloned, characterized, and expressed in E. coli and other hosts [60,[62][63][64], but only a few have been successfully expressed in various host plants (Table S1 in the supplementary material online). Comparative lignocellulosic-digestion studies with mesophilic and hyperthermophilic cellulases and hemicellulases have demonstrated that the functionally homologous hyperthermophilic enzymes can increase saccharification yields and shorten incubation times, and may eliminate the risk of downstream contamination by mesophilic microorganisms competing for fermentable sugars [65,66].…”
Section: Hyperthermophilic Enzymesmentioning
confidence: 99%
“…To date, microbial xylanases have been classified into nine glycoside hydrolase (GH) families: 5,8,10,11,16,26,30,43 and 62 based on the similarity of the catalytic domain sequences (www.CAZy.org). The true β-1,4-acting xylanases with a unique catalytic domain are restricted to GH families 5, 8, 10, 11 and 30.…”
Section: Introductionmentioning
confidence: 99%